Complex drug interactions in an HIV-seropositive heart transplant recipient - Isabelle Sénéchal; Nathalie Châteauvert; Philippe GERVAIS; Pierre Voisine; Michelle Dubois; Mario Sénéchal (KARE Publishing, 2020)
Highly active antiretroviral therapy has led to greater life expectancy for human immun-deficiency virus (HIV)-positive patients. This was a report of 11 years of follow-up of an HIV-seropositive patient who underwent heart transplantation in 2006, with emphasis on the management challenges of complex drug interactions over time.